Interleukin-1 beta gene polymorphisms in patients with fibromyalgia syndrome - Çetin, Buğra; Güleç, Seda; Güleç, Hüseyin; Ulutaş, Özgür; İşbir, Turgay (Journal of Surgery and Medicine, 2022)
Background/Aim: Fibromyalgia syndrome (FMS) has been linked to a genetic background. Although there are conflicting results, it has been suggested that cytokines play a role in FMS etiology. Interleukin (IL)1β is a cytokine that has been linked to FMS symptoms and has been detected in the skin of FMS patients. We aimed to determine the possible relationship between IL1β -31 and IL1β -511 polymorphisms in FMS. Methods: In this cross-sectional study, we included patients who were diagnosed with FMS according to the American College of Rheumatology classification criteria. IL1β -31 (rs 1143627) and IL1β -511 (rs 16944) polymorphism genotyping was conducted in FMS patients (n=33) and healthy controls (n=41) using real-time polymerase chain reaction (RT-PCR). Results: IL1β -511 variations in patients with FMS and control groups were significantly different (P=0.010). The frequency of the IL1β -511 heterozygote AG genotype was significantly higher in controls (P=0.028). Additionally, the frequency of the IL1β -511 wild type A allele was significantly higher in the control group (P=0.003). The IL1β -31 genotypes and allele frequencies were not significantly different between the groups. Conclusion: The IL1β -511 wild type A allele could be a risk-reducing factor for FMS. The present study suggests that genetic variations of the IL1β gene could play an important role in FMS etiology.